Phytoplankton Biodiversity in Two Tropical, High Mountain Lakes in Central Mexico - Estela Cuna; Javier Alcocer; Martha Gaytán; Margarita Caballero (Diversity, 2022)
Lakes El Sol and La Luna, inside the crater of the Nevado de Toluca volcano, Central Mexico, are the only two perennial high mountain lakes [HML] in the country. HML are considered among the most comparable ecosystems worldwide. These lakes are “extreme” environments with diluted, oligotrophic, and cold waters exposed to high UV radiation doses. In this paper, we document the phytoplankton species inhabiting these two extreme tropical ecosystems. The phytoplankton diversity of Lakes El Sol and La Luna is low compared to the global phytoplankton diversity from other Mexican inland waters. Nonetheless, the phytoplankton diversity turned out to be high compared to other HML worldwide, both temperate and tropical. The phytoplankton community in Lake El Sol was formed by 92 morphospecies and in Lake La Luna by 63; in both, the most diverse groups were Bacillariophyceae and Chlorophyceae. All species found in Lake La Luna were present in Lake El Sol, but 29 species present in Lake El Sol were absent in Lake La Luna. Nevertheless, 57% of the most frequent and abundant taxa in Lake El Sol were rare in La Luna, and 47% of the most frequent and abundant taxa in Lake La Luna were rare in Lake El Sol. Associated with their shallowness and polymictic thermal pattern, 87.5% of the Bacillariophyceae morphospecies are tychoplantonic, while the remaining 12.5% are truly planktonic. Dominant taxa were Chlorophyceae in Lake El Sol and Cyanobacteria in Lake La Luna. The most extreme conditions of Lake La Luna (ultraoligotrophy, very low pH, high ultraviolet radiation) most likely explained the differences in the dominant species composition and lower species richness compared to Lake El Sol. Herein, we provide for the first time a taxonomic list of the phytoplankton community of Lakes El Sol and La Luna. This information constitutes a baseline needed to use these HML as sentinels of global and climate change.